2019
DOI: 10.3389/fcvm.2019.00139
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Platelet Function of Metal-Based Nanoparticles Developed for Medical Applications

Abstract: Nanomaterials have been recently introduced as potential diagnostic and therapeutic tools in the medical field. One of the main concerns in relation to the use of nanomaterials in humans is their potential toxicity profile and blood compatibility. In fact, and due to their small size, NPs can translocate into the systemic circulation even after dermal contact, inhalation, or oral ingestion. Once in the blood stream, nanoparticles become in contact with the different components of the blood and can potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 123 publications
0
19
0
Order By: Relevance
“…When NPs are in the bloodstream, they come in contact with various components of the blood and may disrupt the normal function of platelets, causing bleeding or thrombosis. The biocompatibility of NPs with blood elements is a controversial issue [ 178 ]. Overcoming MDRs has evolved to improve antibiotics, and as a result, nanomedicine delivery systems can provide ways to develop antimicrobial nanomedicine.…”
Section: Challenges Of Ag and Au Nps As Antibacterial Nanomedicinesmentioning
confidence: 99%
“…When NPs are in the bloodstream, they come in contact with various components of the blood and may disrupt the normal function of platelets, causing bleeding or thrombosis. The biocompatibility of NPs with blood elements is a controversial issue [ 178 ]. Overcoming MDRs has evolved to improve antibiotics, and as a result, nanomedicine delivery systems can provide ways to develop antimicrobial nanomedicine.…”
Section: Challenges Of Ag and Au Nps As Antibacterial Nanomedicinesmentioning
confidence: 99%
“…In addition, common complications associated with long-term use of central venous catheters are occlusions and catheter-related thrombosis. AgNPs are well known for having antimicrobial properties and unique characteristics that make them very attractive for biomedical applications (Hante et al, 2019). In one of our recent publications, we have demonstrated that AgNPsLA synthesized by our team are able to down-regulate P-selectin and GPIIb/IIIa receptor expression, inhibiting platelet aggregation under flow conditions.…”
Section: Introductionmentioning
confidence: 84%
“…Silver nanoparticles (Ag-NPs) are among the most favored metal NPs due to the multiple functionality as pronounced antimicrobial agent [17][18][19], combined with antifungal effect of Ag-NPs on dermatophytes [20,21], anti-cancer [22], anti-inflammatory [23], antiviral [24], anti-angiogenesis [25] and antiplatelet activities [26], has made them the most used NPs to treat various diseases and infections [27] making them significant in the field of medicine and health care. Ag-NPs also demonstrated good catalytic properties in the field of dye detoxification, heavy metal removal and remediation [28,29].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…It was observed that for NCs smaller than 100 nm, sphere shape NCs displayed higher cellular uptake than nanorods while for NCs larger than 100 nm nanorods exhibits higher cellular uptake followed by spheres [26]. Spherical Ag-NCs, with size within 10 -15 nm possess antiplatelet properties [26] and are less toxic [132].…”
Section: Gamma Irradiation-assisted Synthesis Of Cellulose Nanocrystal-reinforced Gelatine Hydrogelsmentioning
confidence: 99%